KEY GINGIVAL DIMENSIONS AND SHAPES OF MAXILLARY CENTRAL INCISORS IN A MIDDLE EAST POPULATION – A PRELIMINARY REPORT - DR. SHREYA SHETTY; Ms KHAMARUNISSAH SHEIKH; Dr. HASHIM HAMZAH A ALAIDAROOS; Dr. KHLOOD HAMED ALGHAMDI; Dr. OMNIA ASHRAF MOHAMMED ZAGHLOUL (The Bioscan, 2025)
BACKGROUND: The purpose of this study was to evaluate whether a correlation exists between maxillary central incisor tooth shapes and various periodontal parameters, including gingival and periodontal characteristics. MATERIALS AND METHODS: Clinical measurements were recorded for 60 systemically healthy male and female individuals aged 21–35 years. Measurements included crown width (CW), crown length (CL), height of the interproximal papilla (Ph), gingival angle (GA), mesiodistal width (MDW), and contact surface length (CS) of the maxillary central incisors. Based on the crown shape, participants were categorized into three groups: tapered, square, or ovoid. These groups were analyzed for statistically significant differences in the recorded clinical parameters. RESULTS: Statistically significant differences were observed among the three tooth shape groups in papillary height, gingival angle, and contact surface length (P < 0.05). CONCLUSION: Tooth shape is significantly associated with variations in gingival angle, contact surface length, and interproximal papilla height. These correlations may serve as useful clinical guidelines in esthetic planning for restorative and prosthodontic treatments involving the maxillary central incisors.